2021
DOI: 10.1088/2632-959x/abfdd0
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the impact of the bias-dependent charge neutrality point on graphene based multi-transistor applications

Abstract: The Dirac voltage of a graphene field-effect transistor (GFET) stands for the gate bias that sets the charge neutrality condition in the channel, thus resulting in a minimum conductivity. Controlling its dependence on the terminal biases is crucial for the design and optimization of radio-frequency applications based on multiple GFETs. However, the previous analysis of such dependence carried out for single devices is uncomplete and if not properly understood could result in circuit designs with poor performan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 57 publications
1
13
0
5
Order By: Relevance
“…In the subthreshold region, the drain current has exponential dependence on the gate voltage reaching 731 (131) for the MoS2-(ReS2-)ISFET, while in saturation and linear regions the relationship becomes quadratic and linear [25], with values of 47 (30) and 14 (14), respectively. These predictions are in excellent agreement to those experimentally achieved: 713 (126), 53 (35) and 13 (14) in [4] ( [5]). In addition, we have employed this model to determine the change of drain current as a function of the pH in the subthreshold region (Figs.…”
Section: Results and Discussion: Theory Vs Experimentssupporting
confidence: 89%
See 1 more Smart Citation
“…In the subthreshold region, the drain current has exponential dependence on the gate voltage reaching 731 (131) for the MoS2-(ReS2-)ISFET, while in saturation and linear regions the relationship becomes quadratic and linear [25], with values of 47 (30) and 14 (14), respectively. These predictions are in excellent agreement to those experimentally achieved: 713 (126), 53 (35) and 13 (14) in [4] ( [5]). In addition, we have employed this model to determine the change of drain current as a function of the pH in the subthreshold region (Figs.…”
Section: Results and Discussion: Theory Vs Experimentssupporting
confidence: 89%
“…This is consistent with the results achieved by Le et al in [28], who demonstrated a measured SpH-V of 4.4 V/pH for γ = 33 for the particular case of monolayer MoS2-based ISFETs. * Rc represents the metal-2D semiconductor contact resistance, included by connecting lumped resistors to the drain and source terminals [35].…”
Section: Results and Discussion: Theory Vs Experimentsmentioning
confidence: 99%
“…Fuente: (Pasadas et al, 2021) Aunque este trabajo se centra en los GFET, los diseños de RF específicos se pueden adoptar para otras tecnologías 2D ambipolares, como el fosforeno (Das et al, 2014) o los FET MoTe2 (Lin et al, 2014), entre otros. A continuación, resumimos las principales aplicaciones de los GFET en circuitos de RF para la enseñanza en ingeniería.…”
Section: Diseño De Circuitos De Rf Basados En Grafeno Para Futuros In...unclassified
“…Para un GFET de canal largo con buen comportamiento, podemos estimar V Dirac de acuerdo con la Ref. (Pasadas et al, 2021) como:…”
Section: Circuitos Multiplicadores De Frecuencias Basados En Gfetsunclassified
See 1 more Smart Citation